Doing ethics with microbes: toward a queer feminist posthuman framework for bioethics [version 1; peer review: 1 approved, 2 approved with reservations] - Salla Sariola; Tiia Sudenkaarne (Wellcome Open Research, 2024)
The Centre for the Social Study of Microbes (CSSM) at University of Helsinki, Finland is a Wellcome-funded hub for creating new approaches to human-microbial relations. Most urgently, the complex relations between microbes, antimicrobial resistance (in its human-health centered definition, understood as infection and disease now uncurable by antibiotics, threatening human life and wellbeing), animals, environments and climate emergency require new theoretical and methodological approaches. These include a variety of research interest from global fermentation practices and cultures to microbial bioremediation techniques, from aquatic microbes to urban gardens. A key orientation of CSSM is also combining ethnography with artistic and performative practice such as felting, painting, installation, sculpture and audiovisual means, to gain a deeper, more sensory and embodied perspective of our shared lives with microbes. As their agency exists outside textuality, new experimental methodology is needed to engage with it. Thinking with microbes invites many ethical issues that often remain unaddressed in medical and scientific approach. As one of such contributions, we suggest a new framework for bioethics. In a conceptual analysis, a queer feminist posthuman framework aims for radical reorientation of human exceptionalism for more-than-human justice while keeping existing social justice issues between groups of people, such as vulnerabilities cascading around gender and sexual variance, in the same framework. Both a theoretical and practical initiative, seeking to forge solidarity between justice movements, this framework could ground policies relevant to a broader bioethical and philosophical research community, and social scientists studying microbes. This open letter discusses this work at the CSSM.